1999
DOI: 10.1074/jbc.274.49.34924
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and Molecular Basis for Induction of Apoptosis by a p53 C-terminal Peptide in Human Cancer Cells

Abstract: A p53-derived C-terminal peptide induced rapid apoptosis in breast cancer cell lines carrying endogenous p53 mutations or overexpressed wild-type (wt) p53 but was not toxic to nonmalignant human cell lines containing wt p53. Apoptosis occurred through a Fas/APO-1 signaling pathway involving increased extracellular levels of Fas/FasL in the absence of protein synthesis, as well as activation of a Fas/APO-1-specific protease, FLICE. The peptide activity was p53-dependent, and it had no effect in three tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
105
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 43 publications
5
105
0
1
Order By: Relevance
“…27,38 In this study, we showed that this peptide was not toxic to normal colon and normal, as well as, non-malignant breast cells with endogenous wt p53. The peptide selectively induced apoptosis in pre-malignant colon cells with mutant p53 (Fig.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…27,38 In this study, we showed that this peptide was not toxic to normal colon and normal, as well as, non-malignant breast cells with endogenous wt p53. The peptide selectively induced apoptosis in pre-malignant colon cells with mutant p53 (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…27 All peptides were HPLC purified to Ͼ95% pure. Peptide stocks (4 mM) were prepared in sterile distilled water and stored in aliquots at Ϫ80°C.…”
Section: Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…A synthetic peptide derived from the p53 C-terminal domain (peptide 46) was shown to restore the specific DNA binding and transcriptional transactivation function of several hot-spot mutant p53 proteins and rescue the function of endogenous mutant p53 proteins resulting in growth inhibition and cell death by apoptosis (Selivanova et al, 1997;Kim et al, 1999). The observation that C-terminal peptides can restore the DNA-binding activity to isolated core domain proteins indicated that it might directly affect the p53 domain where tumor-derived mutations are clustered.…”
Section: Current Strategies For Mutant P53 Rescuementioning
confidence: 99%